2010
DOI: 10.2319/072309-411.1
|View full text |Cite
|
Sign up to set email alerts
|

A cephalometric study to investigate the skeletal relationships in patients with increasing severity of hypodontia

Abstract: Objectives: To determine the skeletal relationships in patients with hypodontia and analyze the effects of severity and pattern. Materials and Methods: Pretreatment lateral cephalograms from 277 patients with hypodontia, categorized by the number of missing teeth as mild (1-2), moderate (3-5), or severe ($6), were digitized recording angular measurements and ratios and compared with published norms matched for age and gender. Pattern was determined as mandibular, maxillary, bimaxillary, bilateral, anterior, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 22 publications
3
45
1
11
Order By: Relevance
“…So far it was accepted that the presence of the teeth themselves within the alveolar processes mechanically models the volume of the jaws. 12,25 Until recently, data suggestive for a possible molecular underpinning of this phenomenon was however lacking. In their study in mice, Cawthorn et al 26 identified Wnt10a as well as Wnt10b and Wnt6, as potent endogenous regulators of mesenchymal stem cell fate, inhibiting adipogenesis and stimulating osteoblastogenesis through a b-catenindependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far it was accepted that the presence of the teeth themselves within the alveolar processes mechanically models the volume of the jaws. 12,25 Until recently, data suggestive for a possible molecular underpinning of this phenomenon was however lacking. In their study in mice, Cawthorn et al 26 identified Wnt10a as well as Wnt10b and Wnt6, as potent endogenous regulators of mesenchymal stem cell fate, inhibiting adipogenesis and stimulating osteoblastogenesis through a b-catenindependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…12 Therefore, in addition to the description of the dental and general syndromic ED features, the aim in this study was to document the facial phenotypic variations in four families with WNT10A mutations and to give a comprehensive overview of the literature regarding WNT10A mutations, associated conditions and developmental defects.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in vertical jaw relation and mandibular plane inclination in persons with severe hypodontia was observed by Øgaard and Krogstad 25 and Nodal et al 30 Chung et al 31 and Acharya et al 32 found that severe hypodontia had a significant effect on a skeletal relationship.…”
Section: Introductionmentioning
confidence: 93%
“…24,25,[30][31][32] Ogaard and Krogstad 25 concluded that typical dentofacial structure in individuals with a larger number of absent teeth, is due to dental and functional adjustment rather than to an altered growth pattern, but Bondarets and Mc Donald, 24 in Table 2. Significantly reduced value of SNA angle in patients with different number of absent teeth determined in this study, is in compliance with findings of Wisth et al, 27 Roald et al, 35 Sarnäs and Rune 26 and Ogaard and Krogstad, 25 opposite to normal values of this parameter established of Woodworth et al, 23 Nodal et al, 30 Chung et al 31 and Yüksel and Ucem.…”
mentioning
confidence: 99%
See 1 more Smart Citation